The Moral Politics of Inclusion: Social Exclusion and Identity Transformation in Indonesian Community-Based Tourism - Stephanie Theodora Mulyono; Rudy Pramono; Juliana Juliana (Apollo: Journal of Tourism and Business, 2026)
Community-Based Tourism (CBT) is widely promoted in Indonesia as a participatory and empowering development strategy. However, the realities of inclusion and benefit distribution are often shaped by social hierarchies, customary norms, and moral evaluations. This study employs a qualitative, interpretive approach to examine how CBT participation produces both inclusion and exclusion, and how moral and social norms mediate the transformation of local identity. Data were collected through in-depth interviews, participant observations, and document analyses across multiple Indonesian CBT sites. The findings reveal that participation is governed not only by formal rules but also by informal gatekeeping, moral judgments, and social capital, resulting in differentiated access to economic and symbolic benefits. Excluded individuals often experience resentment, silence, and a shift in identity from “hosts” to marginalized subjects. By integrating the moral economy with critical tourism studies, this study advances a relational and politicized understanding of CBT. It moves beyond procedural models of participation to theorize CBT as a field of moral-political contestation, where the distribution of benefits is inseparable from struggles over legitimacy, social recognition, and the very definition of 'community.' This framework provides critical leverage for analyzing social exclusion and identity transformation in tourism development beyond the Indonesian context.